Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1063/1.1778373
|View full text |Cite
|
Sign up to set email alerts
|

Time resolved infrared absorption studies of geminate recombination and vibrational relaxation in OClO photochemistry

Abstract: Ultrafast time-resolved infrared absorption studies of aqueous chlorine dioxide (OClO) photochemistry are reported. Following photoexcitation at 401 nm, the evolution in optical density at frequencies between 1000 to 1100 cm(-1) is monitored to investigate vibrational energy deposition and relaxation along the asymmetric-stretch coordinate following the reformation of ground-state OClO via geminate recombination of the primary photofragments. The measured kinetics are compared to two proposed models for the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…In some cases, however, vibrational energy relaxation proceeds directly from the non-thermal distribution of high frequency modes without redistribution of the vibrational energy. This was observed in CS 2 (aq) 21 and OClO(aq) 22,23 where the energy predominantly relaxes through the asymmetric stretch vibration populated in geminate recombination. Wang et al 25 studied liquid alcohols and demonstrated vibrational energy relaxation in part due to anharmonic coupling to low frequency modes and in part due to a vibrational cascade involving other high frequency modes.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In some cases, however, vibrational energy relaxation proceeds directly from the non-thermal distribution of high frequency modes without redistribution of the vibrational energy. This was observed in CS 2 (aq) 21 and OClO(aq) 22,23 where the energy predominantly relaxes through the asymmetric stretch vibration populated in geminate recombination. Wang et al 25 studied liquid alcohols and demonstrated vibrational energy relaxation in part due to anharmonic coupling to low frequency modes and in part due to a vibrational cascade involving other high frequency modes.…”
Section: Introductionmentioning
confidence: 86%
“…It is instructive to look at vibrational energy relaxation in two limiting cases: a thermal model, sometimes referred to as an anharmonic coupling model, 4,[16][17][18][19][20] and a non-thermal model. [21][22][23] In the thermal model the excess electronic energy after internal conversion is converted into vibrational motion on the potential surface of the electronic ground state. This vibrational energy is assumed to be in thermal equilibrium at a temperature dictated by the heat capacity of the dGMP molecule, and through the Boltzmann distribution most of the vibrational population thus resides in the low frequency modes of the dGMP molecule.…”
Section: Energy Dissipation In Dgmp: Relaxation Pathwaysmentioning
confidence: 99%
“…In the second model, which is known as the non-thermal relaxation model [187][188][189], the vibrational Scheme 2 The structures of adenosine monophosphate, guanosine monophosphate, and a series of methylated xanthines. Hydrogen bond donor sites are highlighted to emphasize their inverse relationship with the molecule's vibrational cooling lifetime (τ vc ), i.e.…”
Section: Vibrational Cooling Dynamics In the Ground Statementioning
confidence: 99%
“…[62][63][64][65][66] It is distinguished from the so-called non-thermal model in which the populations of a small number of high-frequency modes are non-statistical for times long enough to be measured. [67][68][69] In the latter case, the frequency shifts experienced by the excited vibrational modes mainly arise from diagonal anharmonicity.…”
Section: (A) Gmp At Neutral Pdmentioning
confidence: 99%